Prevalence of Undernutrition and Associated Factors: A Cross-sectional Study among Rural Toddlers in Bangka Belitung, Indonesia - Eka Safitri Yanti; Tesza Rezky Permata (International Journal of Advanced Health Science and Technology, 2023)
Malnutrition in toddlers is known to cause disturbances for growth and development. The impact on poor mental development and school achievement and disorders. Conventional tools are often used to predict this risk. On the other hand, the classification of nutritional disorders using the Composite Index of Anthropometric Failure (CIAF) can predict this risk better. The CIAF method is an anthropometric index that combines the three indices of weight/age, height/age, and weight/height to determine the nutritional status of toddlers. Based on Riskesdas data in 2018, the prevalence of stunting under five in Indonesia reaches 30.8% or around 7 million children under five suffer from stunting. This situation is greater than the maximum stunting prevalence limit set by WHO, which is 20%. The prevalence of stunting under five in the Province of the Bangka Belitung Islands is 23.37% where the highest cases occur in West Bangka Regency. However, West Bangka Regency in particular and the Province of the Bangka Belitung Islands in general have not classified malnutrition that occurs based on CIAF. The purpose of this study was to determine the prevalence of undernutrition and the factors that influence it in West Bangka. This study aims to determine the prevalence of undernutrition based on the Composite Index of Anthropometric Failure (CIAF) and the factors that influence it. This research is a descriptive analytic study with a cross sectional design which was conducted for 10 (ten) months in West Bangka Regency. A sample of 155 toddlers was taken by using multistage random sampling technique. The instruments used include a questionnaire about the characteristics, characteristics of parents, and family economy. The measurement tools used to assess nutritional status are in the form of calibrated digital weight and height scales. The results show that 48.4% or almost half of the respondents experience growth and development failure. Most failure to thrive was in the stunting and underweight category (21.3%) and the least was in the wasting only category (1.3%). Type, age of the child, mother's age, mother's education and household income are not variables that affect the nutritional status of children. Further research is needed with a wider scope of variables so that it can be found what are the factors that influence the occurrence of malnutrition